Analysis of the optical properties of the silvery spots on the wings of the Gulf Fritillary, Dione vanillae - Dolinko, Andrés; Borgmann, Luisa; Lutz, Christian; Curticean, Ernest Ronald; Wacker, Irene; Vidal, María Sol; Szischik, Candela; Donie, Yidenekachew; Inchaussandague, Marina; Skigin, Diana; Hölscher, Hendrik; Tubaro, Pablo; et al. (Scientific reports, 2021)
The ventral face of the wings of the butterfly Dione vanillae is covered with bright and shiny silvery spots. These areas contain densely packed ground- and coverscales with a bright metallic appearance reflecting more than 50% of light uniformly over the visible range. Our analysis shows that this optically attractive feature is caused by the inner microstructure of the scales located in these areas. Electron microscopy of cross sections through the scales shows that upper and lower lamina, supporting trabeculae, and topping ridges can be approximated by a ‘circus tent’-like geometry. By simulating its optical properties, we show that a moderate disorder of this geometry is important for the uniform reflection of light resulting in the silvery appearance.